IMPLEMENTASI NILAI-NILAI EKONOMI SYARIAH DI PASAR BELAWA KECAMATAN MALANGKE KABUPATEN LUWU UTARA - Hamzah Kamma; Fasiha Fasiha; Sarwia Sarwia (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2017)
The purpose of this study was to determine the application of Islamic economic values in the Belawa Market, Malangke sub-district, North Luwu Regency. In this study the authors used a type of qualitative descriptive research. Data sources used are primary data sources and secondary data. Primary data obtained from interviews with traders in the Belawa Market, while secondary data sources were obtained from library studies and documents. There are also data collection techniques used through observation, interviews, and documentation. The results of the study show that sharia economic forms in the Belawa Market are those which traders are not responsible for their merchandise and do not apply fairly to their consumers so that consumers feel disadvantaged and wronged by the treatment of traders and consumers who are not comfortable in conducting transactions conducted by traders irresponsible and unfair traders. The application of Islamic economic values in the Belawa Market is not well organized due to a lack of traders' knowledge of Islamic economic values and there are still some traders who cheat in conducting transaction activities and do not pay attention to ethics in trading in accordance with Islamic law.